2009
DOI: 10.1088/0957-4484/20/24/245502
|View full text |Cite
|
Sign up to set email alerts
|

UV and humidity sensing properties of ZnO nanorods prepared by the arc discharge method

Abstract: The UV and humidity sensing properties of ZnO nanorods prepared by arc discharge have been studied. Scanning electron microscopy and photoluminescence spectroscopy were carried out to analyze the morphology and optical properties of the as-synthesized ZnO nanorods. Proton induced x-ray emission was used to probe the impurities in the ZnO nanorods. A large quantity of high purity ZnO nanorod structures were obtained with lengths of 0.5-1 microm. The diameters of the as-synthesized ZnO nanorods were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(93 citation statements)
references
References 25 publications
2
91
0
Order By: Relevance
“…Especially, 2D ZnO nanosheets with mesoporous structures exhibit excellent gas sensing properties including high sensitivity, good selectivity and long-term stability [14,22,23]. Zn 5 (OH) 8 Cl 2 ·H 2 O, as one type of precursors to topologically produce ZnO nanomaterials, has also attracted attention for their gas sensing applications, such as hydrogen gas sensor with highly improved response of 55 at 300°C [14,23]. It has been reported that ZnO nanoparticles can readily agglomerate, owing to their high surface energy [24].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, 2D ZnO nanosheets with mesoporous structures exhibit excellent gas sensing properties including high sensitivity, good selectivity and long-term stability [14,22,23]. Zn 5 (OH) 8 Cl 2 ·H 2 O, as one type of precursors to topologically produce ZnO nanomaterials, has also attracted attention for their gas sensing applications, such as hydrogen gas sensor with highly improved response of 55 at 300°C [14,23]. It has been reported that ZnO nanoparticles can readily agglomerate, owing to their high surface energy [24].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of water with ZnO surfaces is still poorly understood in part due to the complex mechanism of water adsorption on metal oxide surfaces, such as ZnO [31]. However, this effect has been already proposed to be used in the design of humidity sensors based on ZnO bulk [32], TFs [33,34], NWs [35,36], nanorods [37,38], and nanotubes [39].…”
Section: Chemical Composition and Microstructurementioning
confidence: 99%
“…In addition, many UV sensors based on ZnO nanostructures as the sensing material have been reported, however, most of them are characterized by current-voltage measurement, not based on SAW measurment [25,[28][29][30]. In this work, we investigate two ways to improve the UV sensing response based on ZnO/Si SAW devices: one using Sezawa mode instead of Rayleigh mode, and the other using ZnO NRs instead of ZnO film as the sensing material.…”
Section: Introductionmentioning
confidence: 99%